Application of Toxoplasma gondii GRA15 peptides in diagnosis and serotyping. (June 2020) - Li, Runli; Ma, Yeting; Li, Jin; Zhou, Penglai; Zheng, Fuguo; Liu, Qing; Gao, Wenwei
Abstract: Previous studies showed that three clonal strain types (I, II, and III) of Toxoplasma gondii can be distinguished using serotyping based on a series of polymorphic proteins. However, to establish a systematic serotyping method with higher resolution even being equal to that of genotyping, more specific peptide markers are needed. The objective of the present study was to determine the possibility of the polymorphic dense granule protein 15 (GRA15) for diagnosis and serotyping of T. gondii infection. Three different T. gondii GT1 strain GRA15 gene fragments encoding a 584-residue peptide, a 199-residue peptide and a 84-residue peptide were amplified, expressed and purified, respectively. Anti- T. gondii GT1 strain antibodies, anti- T. gondii RH strain antibodies and anti- T. gondii PRU strain antibodies were used for immunoblotting analysis of the three peptides. Western blotting analysis showed that the 584-residue peptide of GT1 strain GRA15 was a potential candidate for serological diagnosis of T. gondii infection. RH strain from GT1 strain could be distinguished by serotyping based on the GRA15199 or GRA1584, and T. gondii GT1 strain could be distinguished from PRU strain by using serotyping based on the GRA1584 . These findings reveal, for the first time, a novel potential role of GRA15-derived peptides in diagnosis and serological differentiation of T. gondii infection. Highlights: The possibility of using Toxoplasma gondii GRA15 peptides for diagnosis and serotyping of T. gondii infection was evaluated. The GRA15584 was a potential candidate for serological diagnosis of T. gondii infection. RH strain from GT1 strain could be distinguished by serotyping based on the GRA15199 or GRA1584 . T. gondii GT1 strain could be distinguished from PRU strain by using serotyping based on the GRA1584 .